Update on Chemotherapy in the Treatment of Urothelial Carcinoma - Carrie Costantini; Frederick Millard (The Scientific World Journal)
Urothelial carcinoma is the fifth most common malignancy diagnosed each year in the United States. Neoadjuvant and adjuvant chemotherapy are given to decrease the risk of recurrent or metastatic disease with the more robust clinical data supporting the former. Bladder preservation utilizes a trimodality approach with maximal transurethral resection followed by concurrent chemotherapy and radiation and is appropriate for select patients. Gemcitabine and cisplatin is the current standard of care for first-line treatment in fit patients with metastatic disease. Optimal second-line therapy remains undefined, and targeted agents are under investigation. Clinical trial participation should be encouraged in patients with urothelial carcinoma of the bladder to help improve treatment regimens and outcomes. Synopsis. Chemotherapy is commonly used in the treatment of urothelial carcinoma of the bladder. This paper will review the role of chemotherapy in the neoadjuvant, adjuvant, bladder sparing, and metastatic settings.